Factors that influence the intention to use online banking: Ecuadorian financial entities - Luna Cajamarca, Daniela; Cedillo Quizhpe, Damaris; Villavicencio Rodas, María Fernanda (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December), 2022)
With the passage of time, the services offered by financial institutions, through the use of technology and the Internet, have become a very useful tool for users, saving time in the process of conducting financial transactions. The purpose of this study is to investigate the factors that influence the intention to use online banking, such as ease of use, perceived quality and perceived hedonic motivation of bank and credit union customers in the city of Machala. A quantitative study was conducted by collecting information through an online survey of 235 convenience customers of banks and credit unions. The results show that the intention to use online banking is positively influenced by ease of use, a closer connection. The study will allow financial institutions to understand the impact of these variables in order to implement strategies that promote the use of online banking, a service that has multiple benefits for both institutions and users.